2013
DOI: 10.1111/dth.12083
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis with cutaneous symptoms in a patient treated with infliximab followed by fatal consequences

Abstract: Leishmaniasis is an infectious disease caused by parasitic flagellates of the genus Leishmania. The authors present a case of 44-year-old man with Crohn's disease treated successfully with infliximab. This case report shows rare visceral leishmaniasis with cutaneous symptoms in an immunocompromised patient. Skin manifestations may occur before or after the visceral infection and they are often diverse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…The first case of a possible association between an anti‐TNF and leishmania infection was reported in 2004 5 . Since then, 49 cases of leishmaniasis in patients treated with an anti‐TNF biologic drug have been reported 6–37 . Six of these 49 cases are included in our multicenter study, and we are also including 32 new cases of anti TNF‐associated CL and MCL 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The first case of a possible association between an anti‐TNF and leishmania infection was reported in 2004 5 . Since then, 49 cases of leishmaniasis in patients treated with an anti‐TNF biologic drug have been reported 6–37 . Six of these 49 cases are included in our multicenter study, and we are also including 32 new cases of anti TNF‐associated CL and MCL 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by meta analysis of 17 studies in HIV infected individuals as the main difference among treatment regimens was in higher mortality rate with antimony use [18.4%, 95% confidence interval (CI) 13.3-25%)] 22 . Published cases of fatal toxicity related to antimonials include severe toxic hepatitis and pancreatitis 7 , fatal arrhythmia 23 , and unexpected sudden death 20 . In pediatric patients, a recent trial showed that N-methylglucamine antimoniate (n = 51) and amphotericin B deoxycholate (n = 50) had similar cure rates (94.1% vs. 94%, respectively) and serious adverse events (SAE) incidence was similar in both groups 24 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α inhibitors are potent immunomodulator drugs with growing use in IBD. Juzlova et al 23 reported a case of 44-year-old man with Crohn's disease treated successfully with infliximab, who developed VL with cutaneous symptoms 23 . He was treated with antimony with a regression of the local findings, but on the 24th day after his admission, the patient suddenly expired due to fatal arrhythmia as a side effect of the treatment with antimony.…”
Section: Discussionmentioning
confidence: 99%
“…CL is a parasite infection caused by leishmania and transmitted by sandfly bites. Estimated incidence of CL is 0.2–0.4 million cases per year . Global burden of CL in children is likely to be underestimated as many infections are misdiagnosed or underreported.…”
Section: Discussionmentioning
confidence: 99%